Circulating ceramides are inversely associated with cardiorespiratory fitness in participants aged 54–96 years from the Baltimore Longitudinal Study of Aging. Issue 5 (2nd May 2016) - Fabbri, Elisa; Yang, An; Simonsick, Eleanor M.; Chia, Chee W.; Zoli, Marco; Haughey, Norman J.; Mielke, Michelle M.; Ferrucci, Luigi; Coen, Paul M.
Summary: Cardiorespiratory fitness (VO2 peak) declines with age and is an independent risk factor for morbidity and mortality in older adults. Identifying biomarkers of low fitness may provide insight for why some individuals experience an accelerated decline of aerobic capacity and may serve as clinically valuable prognostic indicators of cardiovascular health. We investigated the relationship between circulating ceramides and VO2 peak in 443 men and women (mean age of 69) enrolled in the Baltimore Longitudinal Study of Aging (BLSA). Individual species of ceramide were quantified by HPLC–tandem mass spectrometry. VO2 peak was measured by a graded treadmill test. We applied multiple regression models to test the associations between ceramide species and VO2 peak, while adjusting for age, sex, blood pressure, serum LDL, HDL, triglycerides, and other covariates. We found that higher levels of circulating C18:0, C20:0, C24:1 ceramides and C20:0 dihydroceramides were strongly associated with lower aerobic capacity ( P < 0.001, P < 0.001, P = 0.018, and P < 0.001, respectively). The associations held true for both sexes (with men having a stronger association than women, P value for sex interaction <0.05) and were unchanged after adjusting for confounders and multiple comparison correction. Interestingly, no significant association was found for C16:0, C22:0, C24:0, C26:0, and C22:1 ceramide species, C24:0 dihydroceramide, or total ceramides. Our analysis reveals that specific long‐chain ceramides strongly associate with low cardiovascular fitness in older adults and may be implicated in the pathogenesis of low fitness with aging. Longitudinal studies are needed to further validate these associations and investigate the relationship between ceramides and health outcomes.